Determinan Perilaku Pola Asuh Ibu yang Mempunyai Anak Stunting di Kecamatan Subang Tahun 2019 - Arif, Hamid; Susilo, Hadi; Samingan, Samingan (UPT Percetakan dan Penerbitan Universitas Jember, 2023)
Stunting is a condition of growth failure in children under five due to chronic malnutrition, especially in the first 1000 days of birth. The percentage of children stunting in Subang Regency in 2018 reached 3,741, and in Subang, the sub-districts had 104 children. The aim of the study was to determine the factors that influence the behavior of mothers who have stunted children in Subang sub-districts in 2019. This research used the cross-sectional with a quantitative approach using 104 mothers of stunted children under five in Subang sub-district. Data collection using questionnaires carried out during April-June 2019 in the working area of the Sukarahayu and Cikalapa Health Centers Data were analyzed by univariate, bivariate (Pearson chi-square) method and multivariate analysis (regression logistic). The results of the bivariate analysis showed no relationship between age, income, culture, health facilities, health service access and caring behaviour p=0,58; 0,79; 0,29; 0,57; 0,65) dan OR=1,06; 1,20; 1,67; 1,37; 0,80, and there was a relationship between education, knowledge, attitude, sanitation, health workers and behavior (p=0,04; 0,00; 0,02; 0,02; 0,03) dan OR=2,45; 3,60; 2,71; 2,08; 2,64. In conclusion, statistically, knowledge with a p-value of 0.00 OR 95% CI=2.836 (1,411-5,702) is the dominant factor associated with maternal caring behavior after being controlled by attitude and belief.